Application of RIDIT Analysis in Prioritizing Perceived Service Quality Dimensions of Management Graduates in Indian Universities - Pathak, Vivek Kumar; Das, Ashim Kumar; Panda, Rajeev Kumar (Indian Journal of Marketing, 2018)
The transformations in the present socioeconomic situation have compelled the management education in the higher-education sector to behave as a business entity. They are required to focus more on delivering superior quality of educational services to the students. The universities are forced to recognize and give emphasis to the factors which are influencing students’ satisfaction and their future behavioural intentions. Based on these prevailing facts, the present study tried to explore the various dimensions of service quality as perceived by the management graduates of public universities. Further, the study attempted to prioritize the dimensions along with their items to draw meaningful conclusions for the management education sector. The study analyzed survey responses of 401 management graduates using factor analysis in order to diagnose the underlying relationships between the questionnaire items. These resulted in formation of related groups by the items and were named according to their collective characteristics. The study also employed the RIDIT analysis methodology independently to establish the relative importance of each item to the management graduates who participated in the survey. Based on the RIDIT analysis results, a priority ranking was allotted to each individual item. An analysis interpretation was then carried out to find out the extent to which the items grouped into each particular factor tended to have low or high priority rankings. The results of the study may be obliging to the university managers, particularly in a management education setting, to focus their strategies and plan their efforts in line with theÂ findings to gain superior students’/graduates’ satisfaction and favourable future behavioural intentions.